A new endemic species of Trigonachras (Sapindaceae) from Sabah, Malaysia (Borneo) - Buerki, Sven; Davidson, Christopher; Pereira, Joan T.; Callmander, Martin W. (Phytotaxa, 2013)
A new species of Trigonachras from Borneo is described and illustrated. Trigonachras postardanjeisin is endemic to the ultramafic soils of the Tawai Forest Reserve in Sabah, Malaysia (Borneo). It is morphologically close to the widespread Trigonachras acuta but differs by its glabrous inflorescence and infrutescence axes and fruits. The two species also differ by their ecology and distribution. Line drawings are provided for the new taxa, along with discussions of its morphological affinities and preliminary risk of extinction assessment.